2021
DOI: 10.3389/fimmu.2021.645143
|View full text |Cite
|
Sign up to set email alerts
|

T Cell Response Toward Tissue-and Epidermal-Transglutaminases in Coeliac Disease Patients Developing Dermatitis Herpetiformis

Abstract: The reason why only few coeliac patients develop the cutaneous manifestation of the disease, named dermatitis herpetiformis (DH), is still unknown. Epidermal transglutaminase (TG3) has been described as the main autoantigen of humoral immunity in DH but the mechanisms leading to this autoimmune response remain obscure. Here we characterized T cells from skin, gut and peripheral blood of DH and coeliac disease (CD) patients, evaluated the impact of the gluten-free diet on circulating T lymphocytes’ phenotype an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…It has also been reported that the presence of TGM3/IgA deposits activated the migration of neutrophils to the dermal papilla, which efficiently induces subepidermal differentiation through local skin-produced cytokines and chemokines, such as TNF-α and IL-17A, to cleave the adhesion protein from the basement membrane bands, including collagen VII (Russo et al, 2018). In addition, TGM3 is the crucial autoantigen that recognizes T cells in dermatitis herpetiformis (Hradetzky et al, 2015;Caproni et al, 2021). Another study has revealed that TGM3 expression is higher in atopic dermatitis (AD) patients and is positively linked with disease severity, indicating that TGM3 is an autoallergen immune regulator that actively affected skin inflammation in AD (Su et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…It has also been reported that the presence of TGM3/IgA deposits activated the migration of neutrophils to the dermal papilla, which efficiently induces subepidermal differentiation through local skin-produced cytokines and chemokines, such as TNF-α and IL-17A, to cleave the adhesion protein from the basement membrane bands, including collagen VII (Russo et al, 2018). In addition, TGM3 is the crucial autoantigen that recognizes T cells in dermatitis herpetiformis (Hradetzky et al, 2015;Caproni et al, 2021). Another study has revealed that TGM3 expression is higher in atopic dermatitis (AD) patients and is positively linked with disease severity, indicating that TGM3 is an autoallergen immune regulator that actively affected skin inflammation in AD (Su et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…CD’s genetic link to autoimmunity in general, 111 and the presence of gluten‐dependent TG2 autoantibody, 16 is unique among gluten‐associated food allergies including IgE‐associated allergies stimulated by gluten and deamidated gluten 112,113 . Evidence for TG2 being the primary driver of autoimmunity in CD, however, is unconvincing with inconsistent reports of TG2‐specific CD4+ T cells 43,109,114,115 . Similarly, evidence for TG2 IgA causing pathology relevant to CD is weak 116,117 .…”
Section: Pathogenesismentioning
confidence: 99%
“…112,113 Evidence for TG2 being the primary driver of autoimmunity in CD, however, is unconvincing with inconsistent reports of TG2-specific CD4+ T cells. 43,109,114,115 Similarly, evidence for TG2 IgA causing pathology relevant to CD is weak. 116,117 Instead, B cells, plasma cells and TG2…”
Section: Tg2-specific Autoantibodymentioning
confidence: 99%
“…Normally, regulatory T-cells help maintain immune tolerance and prevent both autoimmune and allergic conditions [4][5][6]. The pathophysiology of CD involves activation of helper T-cells 1 (Th1), followed by secretion of pro-inflammatory cytokines, and production of auto-antibodies directed against the enzyme tissue transglutaminase (tTG) [7]. The pathophysiology of IgE-mediated allergies involves activation of helper T-cells 2 (Th2) with a different cytokine profile than that in autoimmunity, which leads to overproduction of allergen-specific IgEs (sIgEs), and activation of sensitization process with the release of allergic reaction mediators by basophils and mast cells [6].…”
Section: Introductionmentioning
confidence: 99%